An improved multi-unit nuclear plant seismic probabilistic risk assessment approach. (March 2018) - Zhou, Taotao; Modarres, Mohammad; Droguett, Enrique López
Highlights: An improved approach is proposed to external event probabilistic risk assessment for multi-unit sites. The issues in dependency modeling in multi-unit seismic PRA are discussed. The issues related to the current discretization-based scheme are highlighted. A case study is developed for the seismic-induced SLOCA for a hypothetical nuclear plant site. Three multi-unit CDF metrics are calculated and discussed in the case study. Abstract: This paper proposes an improved approach to external event probabilistic risk assessment for multi-unit sites. It considers unit-to-unit dependencies based on the integration of the copula notion, importance sampling, and parallel Monte Carlo simulation, including their implementation on standard PRA software tools. The multi-unit probabilistic risk assessment (MUPRA) approach and issues related to the current methods for seismic dependencies modeling are discussed. The seismic risk quantification is discussed in the context of two typical numerical schemes: the discretization-based scheme and simulation-based scheme. The issues related to the current discretization-based scheme are also highlighted. To address these issues and to quantify the seismic risk at the site level, an improved approach is developed to quantify the site-level fragilities. The approach is based on a hybrid scheme that involves the simulation-based method to account for the dependencies among the multi-unit structures, systems and components (SSCs) at the group level of dependent SSCs, and the discretization-based scheme. Finally, a case study is developed for the seismic-induced Small Loss of Coolant Accident (SLOCA) for a hypothetical nuclear plant site consisting of two identical advanced (GEN-III) reactor units. The results from this case study summarize the effects of correlation across multiple reactor units on the site-level core damage frequency (CDF). Three multi-unit CDF metrics (site, concurrent and marginal) were calculated for this case study. It is concluded that based on correlations between the SSCs, the total site CDF metric would be the most appropriate multi-unit CDF metric for seismic risk.